2008
DOI: 10.1097/aog.0b013e318163cd6b
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence of Group B Streptococcus Colonization in a Subsequent Pregnancy

Abstract: More than one third of women had recurrent GBS colonization in a subsequent pregnancy. These findings should assist clinicians in counseling women with GBS colonization about their risk for recurrence, the importance of appropriate prenatal GBS screening in a subsequent pregnancy, and intrapartum antibiotic prophylaxis for unknown GBS status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
0
31
1
1
Order By: Relevance
“…7,8 Approximately one third of women in a subsequent pregnancy will remain colonized with GBS if their previous pregnancy was defined with a heavy colonization of streptococci and a time interval of less than 12 months. 9 In contrast, research studies with longitudinal follow-up in women who are originally GBS negative are lacking. 5 When culture results are not available, the recommendation is to treat based on the existence of risk factors such as delivery less than 37 weeks gestation, ruptured membranes greater than 18 hours, or maternal fever, 1,2 yet GBS status in a previous pregnancy has not been systematically evaluated as a risk factor for recurrent colonization.…”
mentioning
confidence: 95%
“…7,8 Approximately one third of women in a subsequent pregnancy will remain colonized with GBS if their previous pregnancy was defined with a heavy colonization of streptococci and a time interval of less than 12 months. 9 In contrast, research studies with longitudinal follow-up in women who are originally GBS negative are lacking. 5 When culture results are not available, the recommendation is to treat based on the existence of risk factors such as delivery less than 37 weeks gestation, ruptured membranes greater than 18 hours, or maternal fever, 1,2 yet GBS status in a previous pregnancy has not been systematically evaluated as a risk factor for recurrent colonization.…”
mentioning
confidence: 95%
“…Furthermore, in view of the fact that in the surveyed group there were a considerable number of women aged over 30 years (about 33%), some of them could have given birth to children in the times when Streptococcus agalactiae disease prophylaxis was not commonly used. Cheng et al and Turrentine et al are of opinion that, if the phenomenon of GBS colonisation occurs in the first pregnancy, then its return in any subsequent pregnancy is highly probable [7,21]. Nonetheless, as the tests show, it is the primiparas that more frequently did a GBS test (86.4%) and were more aware that it was obligatory (13.6%).…”
Section: Discussionmentioning
confidence: 96%
“…Pregnant women are especially susceptible to infections caused by S. agalactiae because during pregnancy, due to inter alia a high concentration of estradiol, accumulation of glycogen in epithelium cells of the final section of the reproductive organ and an increase in the vaginal pH reaction favour the multiplication of these microorganisms [6]. If the phenomenon of GBS colonisation occurs in the first pregnancy, then its return in any subsequent pregnancy is highly probable [7]. In spite of a mostly asymptomatic course of infection in a pregnant woman, some of them may experience pregnancy and puerperium complications in the form of a premature rupture of the amniotic sac, premature birth, urinary system infection, birth-related fever, and puerperal inflammation of the endometrium [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 251 GBS-positive Taiwanese women, Cheng et al 9 found a 38% risk of recurrent colonization compared with a 15% baseline colonization rate. Among American women, rates of recurrent GBS colonization are reported between 40% and 53%, while among women who tested GBS negative in a prior pregnancy, GBS colonization is 15% to 19%.…”
Section: Discussionmentioning
confidence: 98%
“…Between 13% and 54% of women with an initial positive culture will no longer be colonized at the time of delivery. [5][6][7][8] Recurrent GBS colonization between pregnancies is reported at rates of 38% to 53%, [9][10][11][12] but a clear understanding of the factors influencing GBS colonization over time is lacking. We posited that if microbiological and clinical risk factors for colonization could be identified from an index pregnancy, an opportunity may exist to use this information in the management of a subsequent pregnancy.…”
Section: Introductionmentioning
confidence: 99%